Hereditary angioedema with F12 mutation: factors modifying the clinical phenotype. Issue 12 (10th October 2014) - Charignon, D.; Ghannam, A.; Defendi, F.; Ponard, D.; Monnier, N.; López Trascasa, M.; Launay, D.; Caballero, T.; Djenouhat, K.; Fain, O.; Cichon, S.; Martin, L.; et al.
Abstract Background Hereditary angioedema (HAE) with normal C1 inhibitor (C1Inh) associated with the c.983C>A and c.983C>G mutations of the F12 gene (FXII‐HAE) is a rare condition, and presents with highly variable clinical expression. On the basis of data gathered from a large carrier cohort, we assessed the modifiers affecting the clinical phenotype. Methods We analyzed clinical and biological data recorded from 118 mutation carriers (80 symptomatic and 38 asymptomatic), 58 noncarrier relatives from 40 families, and 200 healthy donors. Disease severity was scored in relation to frequency and location of edema, as well as age at disease onset. To predict FXII‐HAE disease severity, we analyzed the biological phenotype [C1Inh, C4, spontaneous amidase, angiotensin‐I‐converting enzyme (ACE), aminopeptidase P (APP), and carboxypeptidase N/M (CPN)] by means of logistic regression (Akaike information criterion) and odds ratio (OR). Results Meaningful variables contributed to FXII‐HAE, with the kinin catabolism enzymes ACE and CPN exhibiting a significant inverse relationship with disease severity (OR = 0.36, 95% CI 0.23–0.59, P < 0.001; OR = 0.58, 95% CI 0.36–0.91, P < 0.05, respectively). CPN activities were 37.5 (28.5–41.3) nmol/ml/min and 38.5 (32.8–45.6) for FXII‐HAE asymptomatic and symptomatic carriers, respectively, and 37.9 (30.5–43.7) nmol/ml/min for noncarriers. Angiotensin‐I‐converting enzyme activities were 58 (44–76) and 49 (35–59) nmol/ml/min for FXII‐HAE asymptomatic and symptomatic carriers, respectively, and 56 (49–66) nmol/ml/min for noncarriers. Conclusions The FXII‐HAE is associated with modifiers, for example kinin catabolism enzymes, ACE and CPN, different from those recognized in HAE with C1Inh deficiency.